2011
DOI: 10.1177/2041297510394071
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of femtosecond laser-induced front- and rear-side ablation of films

Abstract: Femtosecond laser rear-side ablation, in which the laser beam first passes through the substrate, then irradiates on the film at the substrate–film interface, can be used to fabricate films on a transparent substrate. In this method, the material removal mechanism is different from that in front-side ablation, and the ablation occurs in an enclosed space. The different material removal process in rear-side laser ablation will bring about some unique ablation results. In this paper, the material removal mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…As seen in Table , contrasting with Mn/NiTi‐LDO and NiMnTi‐LDO catalysts, the TiO 2 /NiMn‐LDO displayed the least BET surface area and comparatively larger pore size, which might be relevant with the appearance of new phase of Ni 6 MnO 8 . Besides, compared with Mn/NiTi‐LDO catalyst, NiMnTi‐LDO catalyst exhibited larger surface area, bigger pore volume and smaller pore size, indicated that NiMnTi composite oxide catalyst prepared by calcining LDHs precursors from one step in‐situ method could get more suitable structure which were propitious to NH 3 ‐SCR reaction …”
Section: Resultsmentioning
confidence: 99%
“…As seen in Table , contrasting with Mn/NiTi‐LDO and NiMnTi‐LDO catalysts, the TiO 2 /NiMn‐LDO displayed the least BET surface area and comparatively larger pore size, which might be relevant with the appearance of new phase of Ni 6 MnO 8 . Besides, compared with Mn/NiTi‐LDO catalyst, NiMnTi‐LDO catalyst exhibited larger surface area, bigger pore volume and smaller pore size, indicated that NiMnTi composite oxide catalyst prepared by calcining LDHs precursors from one step in‐situ method could get more suitable structure which were propitious to NH 3 ‐SCR reaction …”
Section: Resultsmentioning
confidence: 99%
“…The vanadium-based catalysts, especially V 2 O 5 /TiO 2 doped with WO 3 or MoO 3 , have achieved great success in selective catalytic reduction (SCR) of NO with NH 3 for their high activity and durability to SO x poisoning. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Nevertheless, this kind of catalyst has a relatively high price, which restricts their wide use in combustion facilities of small to middle scale. On the other hand, the blast furnace slag (BFS), which contains about 20 wt% TiO 2 , is a massive solid waste from the iron-steel industry.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recent studies have shown that incorporation of some metal oxides such as Al 2 O 3 , SiO 2 , Fe 2 O 3 and CeO 2 into TiO 2 support as mechanical promoters enhanced DeNO x catalytic performance of the resulting catalysts because the promoters likely improve the dispersion and thermal stability of catalytic components. [3][4][5][6][7][18][19][20][21][22][23] Especially, TiO 2 -SiO 2 has drawn particular attention because of its induced high DeNO x activity and low SO 2 oxidation activity. The structural advantages from doping SiO 2 are its enhanced dispersion and stabilization effects on anatase TiO 2 and VO x species, together with the formation of more Brønsted acid sites needed for NO reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In order to decrease the thermal effect of laser irradiation during processing, the use of ultrashort pulsed lasers, such as picosecond and femtosecond lasers, are being investigation for scribing processes [8][9]. These lasers are complex and expensive, and regardless of pulse duration, material melting cannot be totally eliminated [5].…”
Section: Introductionmentioning
confidence: 99%